Municipal markets’ recovery plan: the meals market - Sapinho, Marisa Moleiro (2014)
In Portugal, the Municipal Markets’ sector is in decline. The successful cases are rare. Thus, it is necessary to find a feasible solution for this problem. With the presented project, it is intended to suggest possible hypothesis or ideas and to develop one through a Business Plan. The presented idea is related with the adaptation of the Municipal Market of Rato to a dining space. An original idea, in Portugal, that intends to link the concept of tradition, associated to the Municipal Markets, with modernity, by submitting a self-service restaurant with a constant focus on innovation and incorporation to the new industry trends. Taking into consideration not only the current industry trends, but also the customers’ requirements, it is then outlined, at several levels, a strategy with the aim to guide the company in the short and long term. As far as the conclusions are concerned, it is taken into account the funding options as well as the economic and financial feasibility of the project.